2004
DOI: 10.1128/ec.3.1.200-211.2004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Disruption of a Pathway Delivering Copper to Mitochondria onPodospora anserinaMetabolism and Life Span

Abstract: A global depletion of cellular copper as the result of a deficiency in high-affinity copper uptake was previously shown to affect the phenotype and life span of the filamentous fungus Podospora anserina. We report here the construction of a strain in which the delivery of copper to complex IV of the mitochondrial respiratory chain is affected. This strain, PaCox17::ble, is a PaCox17-null mutant that does not synthesize the molecular chaperone targeting copper to cytochrome c oxidase subunit II. PaCox17::ble is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 68 publications
2
62
0
1
Order By: Relevance
“…One of the bestcharacterized aging models with a clear mitochondrial etiology of aging is Podospora anserina. In this filamentous fungus, various mitochondrial pathways, including mtDNA reorganization, 23 mtDNA repair, 24 respiration, 25 ROS scavenging, 26,27 copper metabolism, 28 mitochondrial dynamics 29 and apoptosis, [30][31][32] have been demonstrated to play a role. Recently, an impact of the protein quality control system on aging has been demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…One of the bestcharacterized aging models with a clear mitochondrial etiology of aging is Podospora anserina. In this filamentous fungus, various mitochondrial pathways, including mtDNA reorganization, 23 mtDNA repair, 24 respiration, 25 ROS scavenging, 26,27 copper metabolism, 28 mitochondrial dynamics 29 and apoptosis, [30][31][32] have been demonstrated to play a role. Recently, an impact of the protein quality control system on aging has been demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in contrast to the wild-type strain in which oxygen consumption is very sensitive to cyanide, respiration was $50% resistant to cyanide in the two mutants. In P. anserina, resistance to cyanide has previously been reported in several respiratory mutants partially or completely deficient for complexes III or IV and is due to the induction of an alternative oxidase (AOX) (Dufour et al 2000;Stumpferl et al 2004;Sellem et al 2007). Quantitative RT-PCR experiments revealed that the amount of aox transcripts increased $7-to 20-fold in the mutants compared to the wild type (Table 3).…”
Section: M106pmentioning
confidence: 89%
“…6a). Another inducer of oxidative stress with a role in aging and lifespan control is the micronutrient copper (Osiewacz & Borghouts, 2000;Stumpferl et al, 2004;Scheckhuber et al, 2009), an essential cofactor of different enzymes (e.g. cytochrome c oxidase, Cu ⁄ Zn superoxide dismutase).…”
Section: Impairments Of Mitochondria In Strains Overexpressing Pacypdmentioning
confidence: 99%